20 RAMF Officers improve English competency at UMP - Nor Salwana, Mohammad Idris
PAYA BESAR, 15 August 2022 - A total of 20 Royal Malaysian Air Force (RAMF) officers attended a training Let’s Fly High: Intermediate English for Officers (IEFO) which is implemented with the Centre for Modern Languages (CML) Universiti Malaysia Pahang (UMP) to strengthen English which is synonymous with the language of exploration of various knowledge and is an international communication language.